Translating Images: The Impact of the Image on the Translation of Disney's Alice in Wonderland into Spanish - M.ª Pilar González Vera (Miscelánea: A Journal of English and American Studies, 2012)
The aim of this paper is to analyse the Spanish dubbed version of the 1951 Disney animated film Alice in Wonderland, based largely on Carroll’s Alice in Wonderland and on some passages from Through the Looking-Glass. The paper analyses the relationship between the visual and the verbal elements found throughout this film. Through an analysis of some examples taken from the Spanish dubbed version of the film, this article shows how the visual becomes a crucial issue in the translation of this film where visual elements merge into the verbal discourse.
Keywords: audiovisual translation; Alice in Wonderland; semiotics and visual elements